Climate resilient agriculture: educational/training posters series - Gonsalves, Julian Francis (International Center for Tropical Agriculture, 2016)
These posters are based on key messages derived from a sourcebook of reading/reference materials in a companion production entitled "Towards Climate Resilience in Agriculture for Southeast Asia - An Overview for Decision-makers". They were produced by CIAT with CCAFs funding for an FP1.1 project entitled “Integrated agricultural technologies for enhanced adaptive capacity and resilient livelihoods in climate-smart villages (CSVs) of Southeast Asia”. These posters are designed for use in training or educational events, primarily for starting discussions on important issues facing agriculture in a changing climate. The poster series cover a range of topics/ issues related to climate change in agriculture.They can be used one at a time, and not necessarily in any particular sequence. These pictures can also be enlarged to serve as educational posters, displayed one at a time. They can be used in power point presentations . The illustrations can serve as prototypes for local adaptation and further improvement by local artists. Any use of the illustrations should provide adequate credits to the source. The accompanying sourcebook can be found here: http://hdl.handle.net/10568/71100.